(untitled) (Research, Society and Development, 2022)
This is a scope review protocol on galactogogues used in the management of women with lactation disorders. The objective will be to map the scientific evidence on the use of galactogogue substances in the management of women with lactation disorders who accompany children hospitalized in the Neonatal Intensive Care Unit (NICU). The protocol defines the objectives, eligibility criteria, sources of evidence, graphing methods, results and conclusions related to the Scope Review questions and objectives. It was prepared based on the Preferred Reporting Items for Systematic Reviews and Meta Extension Scoping Rewiew and the Joana Brigs Institute Evidence Synthesis manual. The mnemonic “PCC” will be used, which will deal with Population, Concept and Context, including studies that present data on women with lactation disorders, using galactogogues to correct hypogalactia in the NICU context. Primary and secondary studies will be considered and searches carried out in the second half of 2022, in national and international indexed databases. Those who do not respond to the objective, the research question or do not relate to the population, concept and context listed for the future review will be excluded. Data will be extracted from a developed instrument, containing the following information: author, year of publication, country of origin, objectives/purpose, population and sample size within the source of evidence, methodology, type of intervention, results, main findings related to the scope review question. The results will be presented in a descriptive way, using a flowchart, tables, tables and infographics.